Pembelajaran Doa Harian Sebagai Upaya Membentuk Kebiasaan Islami - Yuris, Evicenna; Khairiah, Dina (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the daily prayer learning process, the formation of Islamic habits, and the challenges faced by early childhood children in the Magrib Mengaji program at Al-Khairi Mosque. The study employed a qualitative case study approach, involving ten children, two instructors, and two parents as informants. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles and Huberman’s interactive model. The results indicate that daily prayer learning is conducted systematically using participatory, multisensory, and contextual approaches. Children actively engage through repetition, independent practice, and real-life application, supported by the roles of teachers and parents in reinforcing Islamic values. This habituation contributes to religious behavior, discipline, responsibility, empathy, and the internalization of gratitude and mutual respect. Challenges identified include limited attention span, the need for more creative teaching methods, inconsistent parental support, environmental distractions at the mosque, and variations in children’s intrinsic motivation. The study confirms that daily prayer habituation is an effective strategy for developing the religious character of early childhood children, requiring collaboration among mosques, instructors, and families, along with creative and contextualized learning methods